2012
DOI: 10.1159/000337171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Serum Prostate-Specific Antigen in Nigerian Men

Abstract: Objective: Lower serum total prostate-specific antigen (PSA) levels (tPSA) have been reported in obese men. It has not been confirmed if this association truly exists in all ethnic groups. Thus, we evaluated the relationship between tPSA and obesity among Nigerian men. Methods: Men aged ≥40 years with tPSA <20 ng/ml and no known prostatic disease were involved. Obesity was defined using the body mass index (BMI) and waist to hip ratio (WHR). Multivariate linear regression was used to investigate the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…Some studies conducted in Nigeria showed no correlation between anthropometrics and PCa or PSA (Ugwumba, Okoh, Echetabu, Udeh, & Nnabugwu, ). Similar findings asserted that overweight and obesity were common among healthy Nigerian men, but was not associated with serum total PSA levels, PCa or BPH development (Ikuerowo, Omisanjo, Bioku, Ajala, & Esho, ). Others found BPH volume to correlate with age but not anthropometrics, and therefore, anthropometrics was not a risk factor in developing BPH (Badmus et al, ).…”
Section: Discussionsupporting
confidence: 66%
“…Some studies conducted in Nigeria showed no correlation between anthropometrics and PCa or PSA (Ugwumba, Okoh, Echetabu, Udeh, & Nnabugwu, ). Similar findings asserted that overweight and obesity were common among healthy Nigerian men, but was not associated with serum total PSA levels, PCa or BPH development (Ikuerowo, Omisanjo, Bioku, Ajala, & Esho, ). Others found BPH volume to correlate with age but not anthropometrics, and therefore, anthropometrics was not a risk factor in developing BPH (Badmus et al, ).…”
Section: Discussionsupporting
confidence: 66%
“…Of the 34 studies providing information on the association between BMI (as a continuous variable) and PSA [25,27,28,, 15 studies (42%) could not be included in the meta-analysis due to insufficient data but were included in an albatross plot [131][132][133][134][135][136][137][138][139][140][141][142][143][144][145]. All included studies are detailed Fig.…”
Section: Continuous Bmimentioning
confidence: 99%
“…Serum PSA tests using chemiluminescence immunoassay (Beckman Coulter Access 2) were carried out on blood samples drawn from the participants before DRE as previously described. [ 21 ] The same method was used for PSA measurements for all the participants. The serum PSA measurement was carried out in the same laboratory of General Hospital, Lagos.…”
Section: Ethodsmentioning
confidence: 99%